2005
DOI: 10.1002/jcb.20458
|View full text |Cite
|
Sign up to set email alerts
|

Induction of an epithelial to mesenchymal transition in human immortal and malignant keratinocytes by TGF‐β1 involves MAPK, Smad and AP‐1 signalling pathways

Abstract: Recent data indicate that transforming growth factor-beta1 (TGF-beta1) can act to promote tumour progression in the late stages of carcinogenesis. The mechanism by which this occurs is unknown although a ligand-induced epithelial-mesenchymal transition (EMT) is thought to be important. In this study, we demonstrate that active Ras is required for TGF-beta1-induced EMT in human keratinocytes and that epidermal growth factor (EGF) can substitute for mutant Ras. EMT was reversed by the removal of TGF-beta1. Under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
153
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 230 publications
(166 citation statements)
references
References 47 publications
8
153
0
3
Order By: Relevance
“…However, during tumor progression, the normal function of TGF-b as a homeostatic negative regulator of cellular proliferation is blunted by activation of oncogenes. Moreover, TGF-b1 expression is sequentially elevated by multiple mechanisms during the progression of multistage carcinogenesis from tumor initiation through to metastasis (Oft et al 2002)-for example, by oncogene-driven AP-1 transcription factor binding to and activation of the TGFB1 gene promoter (Kim et al 1989;Weigert et al 2000;Davies et al 2005) and by latent TGF-b activation within a protease-rich TME (Leitlein et al 2001). Tumor and patient are therefore bathed in excess TGF-b, contributing to an immunosuppressed state.…”
Section: Ligand Expression and Tgf-b Responsiveness In Human Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, during tumor progression, the normal function of TGF-b as a homeostatic negative regulator of cellular proliferation is blunted by activation of oncogenes. Moreover, TGF-b1 expression is sequentially elevated by multiple mechanisms during the progression of multistage carcinogenesis from tumor initiation through to metastasis (Oft et al 2002)-for example, by oncogene-driven AP-1 transcription factor binding to and activation of the TGFB1 gene promoter (Kim et al 1989;Weigert et al 2000;Davies et al 2005) and by latent TGF-b activation within a protease-rich TME (Leitlein et al 2001). Tumor and patient are therefore bathed in excess TGF-b, contributing to an immunosuppressed state.…”
Section: Ligand Expression and Tgf-b Responsiveness In Human Tumorsmentioning
confidence: 99%
“…It has been postulated that SMIs penetrate tumor tissue more easily than antibodies, and this may be true in highly dysplastic tumors, such as pancreatic carcinoma. However, the anti-TGF-b antibody, fresolimumab, was shown to be efficaciously delivered to glioblastoma cells in a clinical setting, presumably owing to breakdown of the blood brain barrier in this neoplastic tissue (Den Hollander et al 2015).…”
Section: Drugs That Block Tgf-b Signalingmentioning
confidence: 99%
“…12,13 AP-1 can also promote invasion and the transition of tumor cells from an epithelial to a mesenchymal morphology, which is one of the early steps in tumor metastasis. 14 Components of AP-1 have also been shown to stimulate EMT. 15 These oncogenic properties of AP-1 are primarily dictated by the dimer composition of the AP-1 family proteins and their posttranscriptional and posttranslational modifications.…”
mentioning
confidence: 99%
“…Many studies of cross-talk between Ras and TGF-h/Smad signaling have been described during the last decade (31)(32)(33)(34)(35). Yue et al (31) reported that TGF-h activated the Ras/MAPK pathway required for the autocrine TGF-h production and Smad1 regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Ras was also suggested as a mediator of pleiotropic TGF-h1 signaling in developing neurons (32). The activation of Ras/MAPK or the presence of oncogenic Ras was shown to enhance TGF-hinduced epithelial-mesenchymal transition (33,34). More importantly, it has been shown that 1a,25(OH) 2 D 3 regulates the MAPK pathway by activating Ras/RAF-1 signaling in muscle cells and in myeloid leukemic cells (17,18).…”
Section: Discussionmentioning
confidence: 99%